EVALUATION AND SYNTHESIS OF NOVEL ANTIPSYCHOTIC COMPOUNDS FROM LUPEOL: Pharmaceutical Science-Chemistry - ANKITA WAL; DR. R.S SRIVASTAVA; DR A.K RAI (International Journal of Life Science and Pharma Research, 2022)
Natural Products traditionally have played an important role in drug discovery and were the basis of most early Medicines. However, despite the promise of these alternative drug discovery methods, there is still a shortage of lead compounds progressing into clinical trials. Plants have been used in treating HIV, TB, antimicrobial and all other diseases. Therefore, the current study was designed to evaluate the antipsychotic potential of lupeol and their semisynthetic derivatives to get a new and potent antipsychotic agent. Lupeol is isolated from bark of crateava nurvala lupeol. Lupeol has many activites like antimalarial, anticancer therefore we have planned to make some derivatives of the lupeol, which may further enhance the antipshychotic activity derivatives were prepared The antipsychotic activity of lupeol derivatives of It is established that they have effective antipshychotic action. Therefore, the current study was designed to evaluate the antipsychotic potential of lupeol and its semisynthetic derivatives. C. nurvala stem bark was extracted by cold maceration with 95% ethanol and concentrated through rotary vacuum evaporator at 400C under reduced pressure. The concentrated ethanolic extract was defatted with petroleum ether and fractionated with chloroform successively. Lupeol derivatives were prepared through a three step reaction with different amines, aliphatic and aromatic moieties. A series of derivatives of lupeol were assayed for antipshychotic activity in actophotometer and compulsive behaviour (Stereotypy) in Plus Maze Model in rats. Few derivatives of lupeol showed more potent activity as compared to the basic molecule, lupeol. The results of the present study clearly indicated that the derivatives and lupeol isolated from C. nurvala and synthetic lupeol analogs possess significant antipsychotic activity. It is thus concluded that lupeol skeleton deserves further investigation for the development of more potent and non-toxic new antipshychotic agents for therapeutic applications.